Working with children from substance-affected families: the community-based group intervention TRAMPOLINE - Sonja Bröning; Diana Moesgen; Michael Klein; Rainer Thomasius (Sociedad Iberoamericana de Pedagogía Social, 2013)
Introduction: Children from substance-affected families show an elevated risk for developing own substance-related or other mental disorders. Frequently, they experience violence, abuse and neglect in their families. Therefore, they are an important target group for preventive efforts. In Germany it is estimated that approx. 2.65 million children are affected by parental substance abuse or dependence. Only ten percent of them receive treatment when parents are treated. To date, no evaluated program for children from substance-affected families exists in Germany. Methods: A new group intervention for children from substance-affected families was developed and is currently being evaluated in a randomized-controlled multicenter study funded by the German Ministry of Health. The development process was simultaneously guided by theory, existing research knowledge and expert opinion. Promoting resilience in children affected by parental substance abuse is a key goal of the program. Results: The TRAMPOLINE manual describes a 9-session addiction-focused, modular group program for children aged 8 to 12 years with at least one substance-using parent. Weekly sessions last for 90 minutes and combine psychoeducational elements with exercises and role play. A two-session parent intervention component is also integrated in the program. Content, structure and theoretical background of the intervention are described. Discussion: TRAMPOLINE is a new interventive effort targeting children from substance-affected families. It is grounded in theory and practice. The results of the research in progress will provide fundamental information on the effectiveness of a structured group prevention program for German children from substance-abusing families. Thus, the study will contribute to creating a broader and more effective system of preventive help for this high-risk target group.